PERCEPTION OF RURAL PRODUCERS ABOUT SYSTEMS INTEGRATED IN AGRICULTURAL PRODUCTION (SIPAs) - Silva, N.G.; Silva, C.V. (Revista Brasileira de Engenharia de Biossistemas, 2020)
There is a growing increase in the demand for food, making it necessary to find the balance between environment conservation and productivity. In this context, this work aimed to evaluate the level of knowledge of rural producers about the SIPAs. The study was conducted with 50 farmers in the region of Pratânia (SP) through the application of semi-open questionnaire. Most rural producers (58%) would apply the intercropping, succession and crop rotation systems. However, many (94%) claimed that they never had a proposal to implement the SIPAs on their properties, and they would not integrate agricultural, livestock and forest production systems (48%). In addition, they do not receive production planning and execution by a farmer (70%). Although not educated on the different forms of production, they agree that it is possible to plant two types of crops in the same area (64%), and that Systems Integrated in Agricultural Production can bring economic benefits (34%), with some caveats. Less than half of respondents said they were unlikely to use Systems Integrated in Agricultural Production on their properties (46%). The implementation of SIPAs is still low due to lack of knowledge, which suggests greater awareness and dissemination of the method by the farming community, suggesting new research on the subject.